Shear Punching Behavior for Flat Slabs with CFRP and Openings - Saad, Zahraa Maitham; Al Amli, Ali Sabah (Engineering, Technology & Applied Science Research, 2025)
This study investigates the punching shear behavior of geopolymer flat slabs with transverse web openings reinforced with Carbon Fiber Reinforced Polymer (CFRP). Shear reinforcement plays a critical role in enhancing the slabs' resistance to punching shear failure, and the addition of transverse web openings allows for service apertures near the columns. In this study, three wooden molds were prepared to test 15 samples of geopolymer concrete under concentrated loading conditions. Each slab had dimensions of 70 cm × 70 cm × 7 cm, with 15 cm × 15 cm × 15 cm columns. The research models were divided into three groups: the first studied the effect of column location, the second examined the influence of openings near the columns, and the third evaluated the impact of CFRP reinforcement. The results showed that transverse web openings reduced the overall punching shear capacity of the slabs due to the loss of concrete in the geopolymer section. However, slabs reinforced with CFRP demonstrated superior performance, which was attributed to the excellent mechanical properties of the material. The full wrapping technique provided the most effective results among the various repair methods tested.